Composer-composer collaboration and the difficulty of intradisciplinarity - Martin Scheuregger; Litha Efthymiou (Airea, 2020)
Research and practice involving parties from different disciplines is of increasing importance in many fields. In the arts, this has manifested itself in both increasing attention on established collaborative partnerships – composers, for example, collaborating with writers, choreographers and directors – and a move towards more overtly cross-, multi-, inter- and/or trans-disciplinary forms of working – a composer working with a physicist, philosopher or psychologist. Composer-composer partnerships are far less common, meaning intradisciplinary collaboration is little explored in relation to practice research in music.